Employee Relationships in the Tourism Industry: A Systematic Literature Review (SLR) and Bibliometric - Faddila, Syifa Pramudita; Senen, Syamsul Hadi (West Science Interdisciplinary Studies, 2023)
This study aims to explore the phenomenon of employee relationships in the tourism industry, as well as provide an overview for managers in dealing with their employees. The study is a systematic literature review using the Scopus database by analyzing 55 articles related to employee relations. Bibliometric analysis is also used with the help of Vos Viewer software to view visualizations of the analysis results. This study shows that employee relationships are critical to the success of any organization. When employees feel valued, supported, and respected, employees are more likely to be more motivated, productive, and loyal.